1983
DOI: 10.1159/000101253
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Radiofrequency Spinal Rhizotomy

Abstract: An anatomical study was conducted to evaluate the emergence of spinal roots at different levels and their relation to the intervertebral foramena. A percutaneous needie was thernnserted in the direction of these roots and their contact studied under direct vision and by X-rays. These results were compared with those obtained in 50 patients who underwent spinal rhizotomies. There is a direct correlation between the anatomy at different levels and the quality of relief obtained after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…32 However, despite its widespread use and well-documented efficacy, this treatment did not seem to be ideal for treating lumbar radicular pain because neurodestructive methods are, in principle, considered inappropriate for the treatment of neuropathic pain (for example, because of denervation dysesthesia and other adverse neurologic effects). 9,35,42,43 In 1998, Sluijter et al 36 introduced an isothermal radiofrequency treatment-PRF-for the relief of chronic pain.…”
mentioning
confidence: 99%
“…32 However, despite its widespread use and well-documented efficacy, this treatment did not seem to be ideal for treating lumbar radicular pain because neurodestructive methods are, in principle, considered inappropriate for the treatment of neuropathic pain (for example, because of denervation dysesthesia and other adverse neurologic effects). 9,35,42,43 In 1998, Sluijter et al 36 introduced an isothermal radiofrequency treatment-PRF-for the relief of chronic pain.…”
mentioning
confidence: 99%
“…132 Although surgical rhizotomy initially led to impressive short-term pain relief in patients with various pain syndromes, 133 in the long term a dramatic loss of efficacy occurred, accompanied by severe adverse effects if substantial denervation had been carried out. 132 Although surgical rhizotomy initially led to impressive short-term pain relief in patients with various pain syndromes, 133 in the long term a dramatic loss of efficacy occurred, accompanied by severe adverse effects if substantial denervation had been carried out.…”
Section: Lumbar Radicular Painmentioning
confidence: 99%
“…In patients with radiating lower limb pain, one prospective 137 and several retrospective studies 10,132,[138][139][140] reported beneficial effects of lumbosacral RF-DRG in 32% to 76% of cases. In a previous retrospective study, 279 patients underwent RF-DRG because of chronic spinal pain radiating to the leg, and an initial success rate of approximately 60% was reported.…”
Section: Evidence For Radiofrequency Treatment Of the Dorsal Root Ganmentioning
confidence: 99%
“…In the 1980s, percutaneous RF treatment was introduced 10. RF treatments are divided into continuous radiofrequency (CRF) stimulation and pulsed radiofrequency (PRF) stimulation using an electromagnetic field.…”
Section: Introductionmentioning
confidence: 99%